2017
DOI: 10.1167/17.5.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allocentric landmarks on primate gaze behavior in a cue conflict task

Abstract: The relative contributions of egocentric versus allocentric cues on goal-directed behavior have been examined for reaches, but not saccades. Here, we used a cue conflict task to assess the effect of allocentric landmarks on gaze behavior. Two head-unrestrained macaques maintained central fixation while a target flashed in one of eight radial directions, set against a continuously present visual landmark (two horizontal/vertical lines spanning the visual field, intersecting at one of four oblique locations 11° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 95 publications
(130 reference statements)
11
49
0
Order By: Relevance
“…This interpretation of the influence of a visual landmark is consistent with other studies in which the accuracy of eye or hand movements towards remembered visual targets was found to be affected by the presence of a displaced landmark (Byrne and Crawford, 2010;Camors et al, 2015;Deubel, 2004;Fiehler et al, 2014;Li et al, 2017;Schütz et al, 2013). Indeed, supporting the idea that a strong assumption for visual stability acts as a prior for landmark stability, studies in which the reliability of the visual landmark was explicitly reduced (by jittering its spatial location) demonstrated that participants' localization responses became noticeably less reliant on the landmark's location (Byrne and Crawford, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…This interpretation of the influence of a visual landmark is consistent with other studies in which the accuracy of eye or hand movements towards remembered visual targets was found to be affected by the presence of a displaced landmark (Byrne and Crawford, 2010;Camors et al, 2015;Deubel, 2004;Fiehler et al, 2014;Li et al, 2017;Schütz et al, 2013). Indeed, supporting the idea that a strong assumption for visual stability acts as a prior for landmark stability, studies in which the reliability of the visual landmark was explicitly reduced (by jittering its spatial location) demonstrated that participants' localization responses became noticeably less reliant on the landmark's location (Byrne and Crawford, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…No correlation was found between the AW as a function of saccade latency (Bharmauria et al, 2020). In the behavioral investigation with the same two animals, we documented that a stable landmark leads to reduction in inaccuracy of gaze endpoints (Li et al, 2017). These results generally agree with previous cue-conflict landmark studies (Neggers et al, 2005;Byrne and Crawford, 2010;Fiehler et al, 2014) and specifically with our use of this paradigm in the same animals, with only slight differences owing to collection of data on different days (Li et al, 2017;Bharmauria et al, 2020).…”
Section: Influence Of Landmark Shift On Behaviorsupporting
confidence: 90%
“…where AW is allocentric weight; d is the projection of TG onto TT' (see below), and D is the magnitude of TT'. The AW values were mainly output between 0 and 1, where 0 refers to absolute egocentric coding and 1 stands for absolute allocentric coding, i.e., the gaze landed on T', completely following the landmark shift (Byrne and Crawford, 2010;Li et al, 2017).…”
Section: Behavioral Recordings and Analysismentioning
confidence: 99%
See 2 more Smart Citations